Acute confusional state-associated factors in older adults admitted to a tertiary hospital emergency unit - Amado Tineo, José Percy (2013)
Acute confusional state is a frequent problem in the elderly and is increased by acute pathologies. Objectives: To determine the frequency of acute confusional state in non-critical elderly emergency service inpatients and to identify associated factors. Design: Cross sectional study. Setting: Emergency Unit, Hospital Nacional Edgardo Rebagliati Martins, Lima, Peru. Participants: Sixty-year-old or older patients hospitalized in an emergency unit. Interventions: Between May and August 2010 and according to procedures of good clinical practices, 172 60-year-old or older patients hospitalized in an emergency unit or their caregivers were interviewed and clinical records were reviewed. Main outcome measures: Acute confusional state detection with the Confusion Assessment Method. Results: The frequency of acute confusional state according to category of elderly was 34.9%: ill 6%, fragile 28% and complex 58% (p <0,001). There was history of dementia in 30% of patients with acute confusional state, cognitive previous deterioration in 45%, previous acute confusional state in 40.2%, functional partial dependence in 46% and total dependence in 39%, cognitive moderate deterioration in 27% and severe in 40%; 41.7% of patients with acute confusional state presented moderate - severe dehydration (p=0.001) and 20% sepsis at admission (p=0.003). The most frequent pathologies at admission were infectious, cardiovascular and metabolic. There was no significant difference in sex, instruction degree, marital status, pluripathology, previous hospitalization, polymedication, nutritional condition, use of urinary or nasogastric tubes, destiny at discharge, or hospital stay. Conclusions: High frequency of acute confusional state existed in elderly patients, being associated factors dementia, previous cognitive deterioration, previous confusional state, functional dependence, complex geriatric category, moderate - severe dehydration and sepsis.